2017
DOI: 10.1055/s-0043-106854
|View full text |Cite
|
Sign up to set email alerts
|

Clowns in Paediatric Surgery: Less Anxiety and More Oxytocin? A Pilot Study

Abstract: Hospital stays and medical interventions are accompanied by worries and anxiety in children and parents. Recent studies show that hospital clowns may reduce anxiety and enhance well-being. However, so far studies are based solely on subjective measures and clowns are usually not integrated in medical routine. With this pilot study, we aim to provide both psychological and physiological evidence of positive effects of clowns' interventions in hospitalized children. In a consecutive randomized intervention-contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 29 publications
(38 reference statements)
3
14
1
1
Order By: Relevance
“…In contrast with our hypotheses and the findings on the mYPAS, we found that children's self-reported mood was unaffected by the clown intervention. While these results jibe with some previous research [e.g., (34)], it could be that in the present study the divergent findings were a function of the assessment method and, in fact, we found only few correlations between these two measures. Specifically, the mYPAS was evaluated by trained observers while children were asked to rate their own mood, which requires a certain level of introspection [see e.g., (78)].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In contrast with our hypotheses and the findings on the mYPAS, we found that children's self-reported mood was unaffected by the clown intervention. While these results jibe with some previous research [e.g., (34)], it could be that in the present study the divergent findings were a function of the assessment method and, in fact, we found only few correlations between these two measures. Specifically, the mYPAS was evaluated by trained observers while children were asked to rate their own mood, which requires a certain level of introspection [see e.g., (78)].…”
Section: Discussionsupporting
confidence: 84%
“…Using the Self Assessment Mannequin [SAM; (33)] to measure valence and arousal of emotional states, Fernandes and Arriaga (28) found that children who received a clown intervention reported higher positive affect than those in the control group, but this was regardless of assessment time (i.e., pre-or post-surgical procedure). In contrast, Scheel et al (34) found no difference between their intervention and control group on emotional valence of the SAM, but instead found an increase in children's salivary oxytocin levels from before hospitalization to after the clown intervention. Because oxytocin may be involved in an allostatic function to counteract experienced stress (35), these results suggest that children who interacted with clowns might have been more at ease.…”
Section: Introductionmentioning
confidence: 82%
“…It was highly correlated with cortisol during a social stress task, and its levels in saliva were negatively associated with anxiety and insecurity 28 . Similar ndings that negative association between higher salivary oxytocin levels and lower anxiety levels were reported in hospitalized children 29 . In youths with anxiety disorder, salivary oxytocin levels were also found to negatively correlate with anxiety symptoms 31 .…”
Section: Discussionsupporting
confidence: 83%
“…More recent research revealed the association between oxytocin and mental health problems. For instance, high oxytocin levels were reported to associate with low anxiety levels in children and adolescents 28,29 . In agreement, urinary oxytocin levels were found to decrease during a social stress task in children and adolescents 30 .…”
Section: Oxytocinmentioning
confidence: 99%
“…A recent German study [16] investigated the ability of clown interventions to induce positive psychological and physiological effects in hospitalized pediatric patients. Thirty-one children (aged 4-13 years) were randomly assigned to a clown group (n = 17) or a control group (n = 14).…”
Section: Effects Of Clown Interventions On Children and Parents In Thmentioning
confidence: 99%